Interactive effects of mGlu5 and 5-HT(2A) receptors on locomotor activity in mice - Halberstadt, Adam L. (Springer-Verlag, 2010)
RATIONALE: Metabotropic glutamate (mGlu) receptors have been suggested to play a role in neuropsychiatric disorders including schizophrenia, drug abuse, and depression. Because serotonergic hallucinogens increase glutamate release and mGlu receptors modulate the response to serotonin (5-HT)(2A) activation, the interactions between serotonin 5-HT(2A) receptors and mGlu receptors may prove to be important for our understanding of these diseases. OBJECTIVE: We tested the effects of the serotonergic hallucinogen and 5-HT(2A) agonist, 2,5-dimethoxy-4-methylamphetamine (DOM), and the selective 5-HT(2A) antagonist, M100907, on locomotor activity in the mouse behavioral pattern monitor (BPM) in mGlu5 wild-type (WT) and knockout (KO) mice on a C57 background. RESULTS: Both male and female mGlu5 KO mice showed locomotor hyperactivity and diminished locomotor habituation compared with their WT counterparts. Similarly, the mGlu5-negative allosteric modulator 2-methyl-6-(phenylethynyl)pyridine (MPEP) also increased locomotor hyperactivity, which was absent in mGlu5 KO mice. The locomotor hyperactivity in mGlu5 receptor KO mice was potentiated by DOM (0.5 mg/kg, subcutaneously (SC)) and attenuated by M100907 (1.0 mg/kg, SC). M100907 (0.1 mg/kg, SC) also blocked the hyperactivity induced by MPEP. CONCLUSIONS: These studies demonstrated that loss of mGlu5 receptor activity either pharmacologically or through gene deletion leads to locomotor hyperactivity in mice. Additionally, the gene deletion of mGlu5 receptors increased the behavioral response to the 5-HT(2A) agonist DOM, suggesting that mGlu5 receptors either mitigate the behavioral effects of 5-HT(2A) hallucinogens or that mGlu5 KO mice show an increased sensitivity to 5-HT(2A) agonists. Taken together, these studies indicate a functional interaction between mGlu5 and 5-HT(2A) receptors.